KONTRIBUSI HUKUM ISLAM PADA PEMBANGUNAN INDONESIA - Wahyuni Ikhwan (Jurnal Syariah Hukum Islam, 2018)
The contribution of Islamic law to the development of law in Indonesia can be seen from two angles of vision. First, the small angle of the involvement of Islamic law in the daily lives of the members of the community who are building itself which ultimately results in a connection with the process above. Second, the angle of causality between Islamic law and the process of legal development in Indonesia. An important thing to note is that Islamic law in contributing to the process of legal development in Indonesia must be able to fix itself first before stepping further into such involvement. This self-improvement encompasses many aspects, especially in terms of its ability to understand and use Ushul Fiqh and Qowaid alfiqhiyyah as a methodology of istinbath al-hukm maximally in the process of taking Islamic law from its sources namely al-Qur'an and al-hadith. This means that the focus of the vision is more on the manhaj (methodology) used by the scholars in the legal process rather than the results achieved. By holding a constructive frame of mind whose paradigm is still relevant to be developed, this will create a "new fiqh" that is able to accommodate new problems that emerge in society dynamically, flexibly and elasticly because the fiqh mindset presented is contextual.